An equation describing diffusivity of liquid atoms by magnetic confinement. (20th May 2015) - Zhang, Kai; Tian, Xuefeng; Bian, Xiufang; Li, Yumin; Liu, Yang
Abstract: In this work, we report an obvious low field-induced magnetic confinement effect on the diffusivity in binary metallic melts under a weak magnetic field. A quantitative description of this nontrivial dynamic behavior is given by a physical analytical model based on the Hall effect, which is in agreement with our experimental results. Meanwhile, a quadratic B dependence of the dynamic viscosity obtained in the same confined environment is observed. Our results show that one can effectively control the atomic diffusion process of metallic melts by the application of magnetic field. Meanwhile, this magnetic confinement effect at atomic scale should provide an important new ingredient to deeply understand the condensed matter physics under the external magnetic field.